Pengaruh Kombinasi Pupuk NPK dan TSP Terhadap Pertumbuhan, Kadar Air dan Klorofil A Gracilaria verrucosa [The Influenced Of NPK and TSP Fertiliter Combination On The Growth, Water Concentration and Chlorophyll A Of Gracilaria verrucosa] - Moch. Amin Alamsjah; Wahyu Tjahjaningsih; Anugraheny Widaratna Pratiwi (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
Abstract Gracilaria verrucosa is one of the most potential seaweed and consist of a high economy value. G. verrucosa had been succed cultivated in pond and it produces gel (Lewmanomont, 1995). Gracilaria cultivation in pond generally needs a wide area, easily infected by moss and shellfish so that obstructs Gracilaria's growth, even decreases it's quality (Aslan, 1998). One of the solution to solve the problem above is cultivate another seaweed G. verrucosa indoor using the combination of NPK and TSP. NPK and TSP are used to increase growth and formation of chlorophyll a which used to fotosintesis process (Anggadiredja dkk., 2006). The absortion of hara element will add nutrient and influenced to the G. verrucosa's quality and quantity. This research uses water concentration measuring because gel content measuring is relatively expensive. The goal of this research is knowing the influence of NPK and TSP to G. verrucosa's growth, water concentration and quantity of chlorophyll a. The result of G. verrocosa shows that daily growth heavy of G. verrocosa in D treatment extremely different (p<0,05) with A, B, C, E and F treatments. The best daily growth heavy of G. verrocosa is in D treatment and the lowest daily growth heavy of G. verrocosa is in A treatment. The result growth length shows that in D treatment extremely different (p<0,05) with A, B, C, E and F treatment. The best growth length is in D treatment and the lowest growth length is in A treatment. The result G. verrucosa's water concentration shows that in C, D and E treatment extremely different (p<0,05) with A, B and F treatment. The best water concentration is in C, D and E treatment. The lowest water concentration is in A, B and F treatment. The result chlorophyll a quantity shows that in B, C, D E and F treatment extremely different (p<0,05) with A treatment. The best G. verrucosa's chlorophyll a quantity is in B, C, D, E and F treatment. The lowest G. verrucosa's chlorophyll a quantity is in A treatment. The conclusion of this research is the combination of NPK and TSP in G. verrucosa seaweed cultivation extremely affect the growth, water concentration and chlorophyll a G. verrucosa with the best dose is 2 g/l and the ratio NPK and TSP is 50%:50%.